2021
DOI: 10.3899/jrheum.210614
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disability to Evaluate the Risk of Arthritis in First-degree Relatives of Patients With Rheumatoid Arthritis

Abstract: Objective The events that occur prior to the onset of rheumatoid arthritis (RA) continue to be delineated. We examined the relationship between self-reported joint symptoms, functional disability, and anticitrullinated protein antibody (ACPA) status in a cohort of first-degree relatives (FDR) of patients with RA who are at risk of future disease development. Methods We studied a cohort of 279 FDR of First Nations (FN) patients with RA who are at increased risk for future RA development, and analyzed data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
3
1
0
Order By: Relevance
“…Indeed, the two most prevalent symptoms retrieved in our study were arthralgia and MCP arthralgia within pre-RA and FDR groups. Moreover, and similar to our study, it was previously reported that arthralgia was higher in FDR than in HC ( 16 ), that joint symmetry was at high risk among arthralgia in FDR from RA patients ( 17 ), and that symmetry takes place as the disease progresses and may be absent at the RA onset ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the two most prevalent symptoms retrieved in our study were arthralgia and MCP arthralgia within pre-RA and FDR groups. Moreover, and similar to our study, it was previously reported that arthralgia was higher in FDR than in HC ( 16 ), that joint symmetry was at high risk among arthralgia in FDR from RA patients ( 17 ), and that symmetry takes place as the disease progresses and may be absent at the RA onset ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Autoantibody data was unavailable for 2 RA patients. Neither of the two FDR groups had clinically detectable RA, although as we previously reported, joint symptoms were prevalent in this population irrespective of their seropositivity status ( 16 ). Of note, the aAb+ FDR group was comprised of 3 individuals who were positive for ACPA only (222.5 ± 83.2 U/mL; mean ± SD), 3 individuals who were positive for RF only (27.9 ± 8.9 IU/mL; mean ± SD), and 4 individuals who were positive for both ACPA (59.6 ± 21.9 U/mL) and RF (231.5 ± 331 IU/mL).…”
Section: Resultssupporting
confidence: 55%
“…Based on this testing, the following 2 groups were included in this study: ACPA + FDR ( N = 53) and ACPA − FDR ( N = 10), which served as the control group. Some of the FDR reported musculoskeletal pain in various locations, as we have documented in other publications [ 7 ]. Venous blood was collected into SST™ serum separation tubes (BD Vacutainer Systems) and centrifuged for serum separation as per the manufacturer’s instructions.…”
Section: Methodssupporting
confidence: 65%